ASSESSMENT OF ACUTE AND SUBACUTE ORAL TOXICITY ELICITED BY ETHANOLIC EXTRACT OF TURNERA APHRODISIACA LEAVES IN ALBINO RATS - BATHULA, NAVEEN KUMAR; CHOWDHURY, BHIMALENDU (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: The medications of plant-based, herb-mineral, and animal sources have been used by the conventional medics to maintain well-being and care for diseases ever since ancient times. The current study aimed to evaluate the acute and subacute toxicities of the ethanolic extract of Turnera aphrodisiaca (TA) leaves in albino rats. Methods: The acute toxicity studies were carried out where the maximum dosage of 5000 mg/kg body mass was used. The outcome reported for 24 h and singly daily for 2 weeks. The rats were weighed and a range of interpretations, for example, behavior, lesions, mortality, or any indication of sickness, was carried out daily once throughout the study. For the subacute study, four groups of ten animals (female rats) received 10% Tween 20 in distilled H2O (as control), and 250, 500, and 1000 mg/kg of newly developed extracts, correspondingly, every 24th h orally for about 4 weeks. At the ending of every study, hematological study and biochemical parameters were assessed. Results: No major variations (p>0.05) were experienced in the comparative organs, body mass, hematological, biochemical parameters, and offensive malfunctions, in comparison to control, with no mortality reported. Hence, the results of the study may direct the outcome that the intermediate-period oral administration of the TA leaves for 4 weeks does not produce toxicity. Conclusion: Due to these results, we may well wrap up that leaves of TA extract are non-toxic in all doses considered in this study and did not created any obvious signs in the acute and subacute oral toxicity studies.